GUEST RECEPTION SYSTEM AND CALCULATION OF RATES STAY ON GUESTHOUSE PARADISE - Sulaeman Sulaeman; Don Elsyahfitra, Skom Don Elsyahfitra, Skom (Jurnal Sistem Informasi, 2002)
A company is required by the user so that he can move markets as quickly as possiblein providing information or data needed by the user's market. Lodging is at oneneeded a computerized system that is integrated, so there are no errors in income orreports to the Chairman.Given the computer-based systems are expected to be able to provide service andsatisfaction for service users Lodging. Designed system can speed up the process ofdata entry process for Lodging Report.